Functional abnormalities in thyroid status (euthyroid sick syndrome) in somatic pathology - V. A. Kichigin; I. V. Madyanov (Лечащий Врач)
The paper analyzes the frequency of euthyroid sick syndrome (ESS) and its types in various severe somatic diseases. 1008 patients who are on hospital treatment in specialized medical institutions were examined. The conclusion is made about the wide prevalence of ESS in somatic patients (36.5%), the formation of this syndrome and its individual types is a reflection of the severity of the underlying disease.